Model of performance evaluation for school supervisors in the academic field - Lia Yuliana; Mohd Faiz Mohd Yaakob (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2022)
This research aimed to find out evaluating model of the performance of school supervisors in the field of academic supervision in improving the quality of high schools in Yogyakarta. This research used the Research and Development method. In the preliminary trial, 4 education experts and practitioners, a small-scale trial applied to 6 supervisors and in the implementation stages 20 high school supervisors were involved. The data collection technique used was the Delphi technique while the data validity used was expert judgment techniques and quantitative analysis with descriptive analysis techniques. The data were analyzed using descriptive statistics. The results show that the procedure for developing a performance evaluation model was done by implementing procedural development research. Based on these data, the PPE model is very feasible to be used by the education office in evaluating the performance of school supervisors and was declared very feasible by experts, which means that this model can be used by stakeholders.